2020
DOI: 10.1590/1807-1929/agriambi.v24n3p209-215
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent drying of clove basil leaves: Process optimization and essential oil yield

Abstract: This study investigated the effect of a drying method with intermittent ratios on the effective drying time, specific energy consumption and essential oil yield of clove basil (Ocimum gratissimum L.) leaves. The drying tests were conducted at the Postharvest Laboratory of Medicinal, Aromatic and Condiment Plants, from the Departamento de Engenharia Agrícola of the Universidade Federal de Viçosa, Viçosa, MG, Brazil (20° 46’ 13.5” S; 42° 52’ 23.3” W, and altitude of 645 m) in October and November 2017. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…De Suza et al [24] showed that an air-drying temperature higher than 50 • C causes significant decreases in the content of the essential oil of clove basil leaves. However, other authors found that the highest essential oil content in dry Piper umbellatum L. leaves is obtained when the air-drying temperature does not exceed 40 • C [25]. On the basis of the presented data it can be concluded that the quantity and quality of oils and other bioactive compounds are most affected by the drying method and drying temperature.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…De Suza et al [24] showed that an air-drying temperature higher than 50 • C causes significant decreases in the content of the essential oil of clove basil leaves. However, other authors found that the highest essential oil content in dry Piper umbellatum L. leaves is obtained when the air-drying temperature does not exceed 40 • C [25]. On the basis of the presented data it can be concluded that the quantity and quality of oils and other bioactive compounds are most affected by the drying method and drying temperature.…”
Section: Introductionmentioning
confidence: 58%
“…Sublimation and vacuum drying were carried out to obtain a constant dried material humidity of 10%.We did not carry out convection drying at 20 • C, because this kind of drying at such low temperature is ineffective, takes a long time, can lead to the development of microorganisms and often does not allow to achieve an adequate level of moisture content after drying. The drying temperature was selected on the basis of the literature data mentioned in the introduction [21][22][23][24][25].…”
Section: Drying Methodsmentioning
confidence: 99%
“…Extensive research has explored alternative approaches to high temperature drying (Bala, 2016;Onwude et al, 2016;Tiwari, 2016;Regal et al, 2020;Souza et al, 2020). However, grains are extremely sensitive to heat (Oliveira, 2013), and inadequate drying can negatively impact qualitative factors such as acidity, protein levels, germination, and appearance.…”
Section: Introductionmentioning
confidence: 99%